CYTOLOGICAL EVALUATION OF OTIC EXUDATES OF DOGS WITH BACTERIAL OTITS EXTERNA - R, Umamaheshwarry; Sivaraman; E., Venkatesakmar; P., Balachandran; D., Sumathi; K., Sasikala; M., Sasikala (Indian Journal of Veterinary Sciences and Biotechnology, 2023)
This study was conducted on a total of 71 dogs with signs of otitis whose cytology was collected and evaluated to characterize the findings which can be used as a diagnostic aid for otitis externa in dogs. Cytology of the 10 normal dogs showed presence of non-nucleated keratinised epithelial cells. These epithelial cells were mostly found as sheets or appeared rolled up and 5 samples (50%) had Malassezia species. The 71 clinical samples showed majority with cocci and neutrophils (26.8%) followed by rods and cocci (21.1%), cocci alone (14.1%), rods and neutrophils (12.7%), mixed population with cocci, rods and neutrophils (11.3%), cocci and Malassezia (8.5%), rods alone (5.5%).